(untitled) (Research, Society and Development, 2021)
Introduction: Eating disorders, if not treated, become vicious circles that can significantly impact the social life of the individual, since he ends up isolating himself from living with other people because of his concern exacerbated with food and body image. Objective: to analyze the relationship between nutrition and self-image disorders in adolescents. Methodology: For this study, we opted for a research in the modality of integrative literature review. The collection of information for bibliographic research will be through the exploration of the database of the Virtual Health Library (VHL), Virtual Electronic Scientific Library (SCIELO) and Latin American and Caribbean Literature on Health Sciences (LILACS). Results and Discussion: It is known that the period of adolescence is characterized by several morphological alterations that are regulated by the maturational process. Among these changes, there is an increase in body fat and lean mass in girls and boys, respectively. The non-acceptance of these pubertal characteristics may have repercussions on problems in the construction of the body image of the young person. Conclusion: With the development of this study, many details and questions about self-image disorders developed among adolescents can be known, considering that this is an increasingly evident problem in today’s society.